Antistatic polyamide compositions and articles containing same
Patent Information
- Application Number
- JP2023561098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-08-05
- Filing Date
- 2022-04-04
- Publication Date
- 2025-03-12
AI Technical Summary
Semi-crystalline polyamides exhibit anisotropic mold shrinkage and dimensional instability due to crystallization, and fibrous fillers like glass fibers exacerbate this effect, leading to issues such as static charge buildup, which can damage electronic components, attract dust, and interfere with sensitive devices.
A polyamide composition comprising a polyamide polymer, electrically conductive materials (like carbon fibers or carbon nanotubes), and glass fillers with a three-dimensional structure, balanced to achieve isotropic mold shrinkage and antistatic properties, reducing surface resistivity to the range of 10^5 to 10^12 Ω/sq.
The composition provides improved dimensional stability, reduced mold shrinkage, and effective static charge dissipation, making it suitable for electronic applications with tight tolerances and ensuring optimal functionality.
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 171216, filed April 6, 2021, and European Patent Application No. 21189881.6, filed August 5, 2021, the entire contents of which are incorporated herein by reference for all purposes.
[0002] The present invention relates to antistatic polyamide compositions and to articles, such as molded articles, especially portable electronic equipment parts, that comprise or are made from such polymer compositions. [Background technology]
[0003] Semicrystalline polyamides have excellent mechanical properties and processability, making them suitable for a variety of applications where good mechanical performance is required. Polyamide moulded articles are widely used in the engineering sector, especially in electronic and automotive components. Due to the demand for moulded articles with high mechanical strength while being lightweight, these articles are generally reinforced with fillers, especially fibrous fillers. Polyphthalamides are valued for their high temperature performance, especially due to their high glass transition temperature Tg and high melting temperature Tm.
[0004] However, semi-crystalline polyamides exhibit anisotropic mold shrinkage as a result of crystallization, and fibrous reinforcing fillers such as glass fibers amplify this effect. In addition, the dimensional stability, such as the coefficient of linear thermal expansion "CLTE" or moisture expansion, is also anisotropic, due to the morphology of the semi-crystalline polymer and the high aspect ratio of the reinforcing fillers.
[0005] Polyamides, like most plastic resins, are insulating materials. Indeed, plastic resins are often considered for use as electrical insulating materials because they typically do not readily pass electrical current and are generally fairly inexpensive compared to other known insulating materials. While many known plastics are durable and heat resistant enough to provide at least some degree of electrical insulating effectiveness, many such plastics are problematic due to the buildup of static charges on the surface of the material.
[0006] Such surface charge build-up can be undesirable for a variety of reasons: such materials can discharge very quickly and, depending on the circumstances, can damage electronic components or cause a fire or explosion; sudden static discharges can also be a nuisance to people using the materials.
[0007] Even if sudden static discharges are not a problem, dust particles are typically attracted to electrostatically charged materials and will accumulate. Additionally, static electricity can interfere with sensitive electronic components or devices, etc.
[0008] Resistivity can be defined as including surface resistivity and volume resistivity. When volume resistivity is in the appropriate range, it provides an alternative path by which charge can dissipate (usually along the surface). In fact, surface resistivity is typically the primary focus of electrostatic discharge ("ESD") polymeric materials.
[0009] Surface resistivity is the electrical resistance measurement (typically measured in Ohms per square or "Ω / sq") measured on the surface of a material at room temperature. 5 Below Ω / sq, the surface of the composition has little insulating ability and is generally considered to be conductive. Such compositions are generally poor antistatic polymeric materials because they bleed off too quickly.
[0010] Surface resistivity is 10 12If the surface resistivity is greater than Ω / sq, the surface of the composition is generally considered to be an insulator. In certain applications, such compositions are also insufficient as antistatic materials because the surface does not have the necessary amount of conductivity to dissipate the static charge. Typically, a surface resistivity of about 10 5 ~10 12 Ω / sq, a charge in contact with the surface quickly dissipates or "decays." Additional information on evaluating surface and volume resistivity can be found in US Standard Test Method D257. Polymer compositions can be made conductive by adding conductive additives. These conductive additives can include carbon fiber, carbon black, carbon nanotubes, graphene, or graphite. These conductive additives can also include surfactants, salts, conductive organic polymers, and conductive inorganic polymers. Summary of the Invention
[0011] It is therefore an object of the present invention to provide a polyamide composition for use in producing polyamide-based articles, preferably molded articles, having anti-electrostatic (ESD) properties and suitable dimensional stability, which combination of properties makes such articles suitable for electronic applications, in particular portable electronic components, which have tight dimensional tolerances and require ESD properties for optimal functionality.
[0012] The present invention solves the problem of anisotropic mold shrinkage and dimensional change (low warpage) in polyamide-based molded parts (such as parts of portable electronic devices) that have very tight dimensional tolerances. "Warpage" refers to the deformation of a molded part in one or more directions that can be caused by the anisotropic shrinkage of the resin during molding.
[0013] The present invention also solves the problem of insufficient dissipation of static electricity in polyamide-based articles or devices that accumulate static charges generated during operation by promoting the slow dissipation of these charges. Without the conductive material, the polyamide-based article or device would be insulating and no dissipation of charge would occur. On the other hand, too much conductive material would cause the polyamide-based article or device to have too low resistivity (too conductive), which could result in the article or device being grounded and inhibiting its performance.
[0014] A first aspect of the present invention relates to a polyamide composition comprising a polyamide polymer, a conductive material, and a glass filler having a three-dimensional structure characterized by an average length of up to 500 microns.
[0015] The polyamide composition is at least 20 weight percent (wt%) of a polyamide polymer; greater than 1% and up to 20% by weight of a conductive material, including carbon fibers, carbon nanotubes, or any combination thereof; 20% to 60% by weight of a glass filler having a three-dimensional structure characterized by an average length of up to 500 microns, the glass filler comprising at least 20% by weight of glass flakes; Including, These weight percentages are based on the total weight of the polyamide composition.
[0016] The specific polyamide composition is at least 20 weight percent (wt%) of a polyamide polymer; greater than 1% and up to 20% by weight of a carbon-based conductive material, including carbon fibers, carbon nanotubes, or any combination thereof; 30% to 55% by weight of a glass filler consisting of glass flakes; Including, These weight percentages are based on the total weight of the polyamide composition.
[0017] The polyamide composition may further comprise optional reinforcing agents different from the glass filler, and / or optional additives such as heat stabilizers, lubricants, impact modifiers, UV stabilizers, pigments, and the like.
[0018] A second aspect of the invention relates to a process for producing a polyamide composition according to the invention, said process comprising melt blending a polyamide polymer, an electrically conductive material, a glass filler, an optional reinforcing agent different from the glass filler, and optional additives such as heat stabilizers, lubricants, impact modifiers, UV stabilizers, pigments, etc.
[0019] A third aspect of the present invention relates to a molded article comprising or produced from the polyamide composition according to the invention.
[0020] A fourth aspect of the present invention relates to an electronic device part, preferably a portable electronic device part, comprising or made from the polyamide composition according to the present invention.
[0021] A fifth aspect of the present invention relates to the use of the polyamide composition according to the invention for producing molded articles, such as portable electronic device parts.
[0022] Another aspect of the invention relates to a method for reducing the surface or volume resistivity and also reducing mold shrinkage and / or warpage of a polyamide-based molded article comprising blending a polyamide polymer with a conductive material, a glass filler, and optionally additives to form a molding composition and then molding, preferably injection molding, the molding composition to form a molded article.
[0023] The various aspects, advantages and features of the present invention will be more readily understood and appreciated by reference to the detailed description and examples.
[0024] definition As used herein, certain terms are intended to have the following meanings.
[0025] As used herein, polyamides are typically obtained by polycondensation between at least one aromatic or aliphatic saturated diacid and at least one aliphatic saturated or aromatic primary diamine, lactam, amino acid, or a mixture of these different monomers.
[0026] As used herein, polyphthalamide (PPA) is typically obtained by polycondensation between at least one diacid and at least one diamine, where at least 55 mol % of the diacid moieties of the repeat units in the polymer chain are terephthalic acid and / or isophthalic acid, and the diamine is aliphatic.
[0027] As used herein, an aliphatic polyamide polymer comprises at least 50 mole percent repeat units having an amide bond (-NH-CO-) and no aromatic groups, in other words, both the diacid moiety and the diamine, lactam, or amino acid moiety that form the repeat units of the polyamide by polycondensation do not comprise aromatic groups.
[0028] As used herein, a "semicrystalline" polyamide has a heat of fusion ("ΔH") of at least 5 joules per gram (J / g) as measured using a differential scanning calorimeter at a heating rate of 20° C. / min. f "). Similarly, as used herein, an amorphous polyamide has a ΔH of less than 5 J / g as measured using a differential scanning calorimeter at a heating rate of 20° C. / min. f Equipped with ΔH f can be measured according to ASTM D3418. In some embodiments, ΔH f is at least 20 J / g, or at least 30 J / g, or at least 40 J / g.
[0029] As used herein, when referring to the "glass transition temperature," Tg, and the "melting temperature," Tm, for the polyamide in the polyamide composition, Tg and Tm are preferably measured according to ASTM D3418 unless otherwise specified.
[0030] The term "nano" as used herein refers to three-dimensional structures, such as tubes, sheets, flakes, dics, spheres, or any other three-dimensional structures, having at least one dimension smaller than about 0.1 micrometers (<100 nanometers) and an aspect ratio from longest dimension to shortest dimension of about 50:1 to about 5000:1. The dimensions of nano three-dimensional structures can be determined by direct measurement on micrographs obtained by dynamic light scattering (DSL) and / or scanning electron microscopy (SEM).
[0031] As used herein, the selection of one element from a group of elements means - the selection of two elements or the selection of several elements from the group, - selection of an element from a subgroup of elements consisting of a group of elements from which one or more elements have been removed; Also explicitly stated.
[0032] In the following text of this specification, any description, even if described in relation to a specific embodiment, is applicable to and interchangeable with other embodiments of the present disclosure. Each embodiment so defined can be combined with another embodiment unless otherwise indicated or clearly incompatible. In addition, it should be understood that the elements and / or features of the compositions, parts or articles, processes, methods, or uses described herein can be combined, explicitly or implicitly, with other elements and / or features of the compositions, parts or articles, processes, methods, or uses in any possible manner, without departing from the scope of this specification.
[0033] As used herein, the recitation of a range of values for a variable defined by a lower limit or upper limit, or by lower and upper limits, also includes embodiments in which the variable is selected within that range of values, excluding the lower limit or excluding the upper limit, or excluding the lower and upper limits, respectively. Any recitation herein of numerical ranges by endpoints includes all numbers subsumed within the recited range, as well as the endpoints of the range, and equivalents thereof.
[0034] The term "comprising" (or "comprises") encompasses "consisting of" (or "consisting essentially of") as well as "consisting of." As used herein, "consisting essentially of" in reference to a composition means that the composition contains less than 1 wt.%, or less than 0.5 wt.%, or less than 0.1 wt.%, or less than 0.05 wt.%, or less than 0.01 wt.%, of any component not expressly listed, said wt.% being based on the total weight of the composition.
[0035] Use of the singular form "a" or "one" herein includes the plural unless specifically stated otherwise. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] It has surprisingly been found that when the polyamide composition according to the invention comprises a polyamide polymer, an electrically conductive material, a glass filler, an optional reinforcing agent different from the glass filler, and optional additives, the resulting polyamide composition gives rise to polyamide-based moulded articles with antistatic properties, improved dimensional stability (CLTE) and improved shrinkage and / or warpage properties whilst exhibiting adequate mechanical performance.
[0037] Molded articles comprising or produced from such polyamide compositions according to the invention exhibit nearly isotropic mold shrinkage and / or low warpage, as well as nearly isotropic CLTE (coefficient of linear thermal expansion). Furthermore, the volume resistivity is such that molded articles comprising or produced from such polyamide compositions according to the invention are electrostatically dissipative (ESD). This combination makes the polyamide compositions according to the invention suitable for electronic applications that have tight dimensional tolerances and require ESD properties for optimal function. Preferably, molded articles comprising or produced from such polyamide compositions according to the invention are electronic equipment components.
[0038] In some embodiments, the polyamide-based molded article or electronic component has a viscosity of at least 1·10 +5 Ω.cm, or at least 1.5·10+5 Ω.cm and / or 5·10 +12 Ω.cm or less, or 3·10 +12 Ω.cm or less, or 1·10 +12 In some embodiments, the polyamide-based molded article or electronic component has a volume resistivity of 1·10 Ω·cm or less (measured according to ASTM D257). +5 Ω.cm to 5·10 +12 The volume resistivity can therefore be adjusted over at least about seven orders of magnitude by selecting a conductive material with a specific volume resistivity and varying the content of the conductive material in the polyamide composition used to produce the molded article.
[0039] In some embodiments, the polyamide-based molded article or electronic component according to the present invention has a % transverse mold shrinkage determined according to ISO 294 (ASTM D955) of less than or equal to 0.5%, or less than or equal to 0.47%, or less than or equal to 0.45%, or less than or equal to 0.44%.
[0040] In some embodiments, the polyamide-based molded article or electronic component according to the invention has a ratio of machine direction mold shrinkage to transverse direction mold shrinkage of greater than 32%, or greater than 35%, or greater than 40%, or greater than 45%, or greater than 50%, or greater than 55%, or greater than 60%, where machine direction and transverse direction mold shrinkage (%) are determined according to ISO294 (ASTM D955).
[0041] In some embodiments, the polyamide-based molded article or electronic component according to the present invention has a warpage of 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.18 or less, where warpage is the absolute value of the percent shrinkage in the cross direction minus the percent shrinkage in the machine direction of the molded article or electronic component comprising the polyamide composition, both % shrinkages being preferably determined according to ASTM D955.
[0042] In some embodiments, a polyamide-based molded article or electronic component according to the present invention obtained by molding a polyamide composition containing 20 wt. % of at least one polyamide polymer, more than 1 wt. % up to 20 wt. % of a conductive material, at least 20 wt. % of glass flakes as at least a glass filler, optional reinforcing agents, and optional additives (e.g. heat stabilizers, lubricants, impact modifiers, UV stabilizers, pigments, etc.) has a lower warpage (%) compared to a similar composition in which the glass flakes are replaced by glass fibers.
[0043] In some embodiments, polyamide compositions according to the invention contain no more than 5 wt.%, preferably no more than 2 wt.%, and more preferably no more than 1 wt.% of polymers other than polyamide polymers.
[0044] In some embodiments, the polyamide composition according to the invention consists essentially of a polyamide polymer, an electrically conductive material, a glass filler, an optional reinforcing agent different from the glass filler, and optional additives as described herein, such as heat stabilizers, lubricants, impact modifiers, UV stabilizers, pigments, etc. The term "consisting essentially of" in reference to a polyamide composition means that the composition contains less than 1 wt.%, or less than 0.5 wt.%, or less than 0.1 wt.%, or less than 0.05 wt.%, or less than 0.01 wt.%, of any component not expressly recited therein, said weight percentages being based on the total weight of the polyamide composition.
[0045] Polyamide Polymer The polyamide composition comprises at least 20% by weight of at least one polyamide polymer, based on the total weight of the polyamide composition.
[0046] The polyamide polymer in the polyamide composition may comprise a semi-aromatic polyamide. In such a case, the polyamide polymer in the polyamide composition may comprise a semi-aromatic polyamide selected from the group consisting of PA10T / 10I; PA10T; PA6T / 6I; PA6T; PA9T; PA12T; PA10T / 66; PA6T / 66; PA6,I; PA12I; PAMXD6; PAPXD10; and any combination thereof.
[0047] The polyamide polymer in the polyamide composition can comprise or consist essentially of at least one polyphthalamide. In such cases, the polyamide polymer in the polyamide composition can comprise or consist essentially of at least one polyphthalamide selected from the group consisting of PA10T / 10I; PA10T; PA6T / 6I; PA6T; PA9T; PA12T; PA10T / 66; PA6T / 66; PA6,I; PA12I; and any combination thereof.
[0048] The polyamide polymer in the polyamide composition may comprise an aliphatic polyamide. In such a case, the polyamide polymer in the polyamide composition may be selected from the group consisting of PA610; PA612; PA1010; PA12; PA510; PA66; PA1012; and any combination thereof.
[0049] The content of the at least one polyamide polymer in the polyamide composition is at least 20 wt%, or at least 25 wt%, or at least 30 wt%, based on the total weight of the polyamide composition.
[0050] The content of polyamide polymer in the polyamide composition may be up to 89.9 wt%, or up to 85 wt%, or up to 80 wt%, or up to 75 wt%, or up to 70 wt%, or up to 65 wt%, based on the total weight of the polyamide composition.
[0051] In some embodiments, the polyamide composition may include a plurality of separate polyamide polymers according to the above description. In such cases, the total content of the separate polyamide polymers is within the ranges described above. A specific example of such an embodiment is when the polyamide polymer comprises or consists essentially of a combination of PA6,10 and PAMDX6. Another example of such an embodiment is when the polyamide polymer comprises or consists essentially of a combination of PA10T / 10I and PAMDX6. PAMXD6 polymer is a polymer made from adipic acid and metaxylylenediamine (commercially available as IXEF® polyarylamide, among others, from Solvay Specialty Polymers USA, LLC).
[0052] One of the polyamide polymers in the polyamide composition (e.g., PAMXD6 polymer) may be a polymer carrier to form a masterbatch into which additives and / or conductive materials are mixed prior to making the polyamide composition. In such a case, the weight content (wt%) of such polyamide (e.g., PAMXD6) used as the masterbatch polymer carrier should be less than the weight content (wt%) of the other polyamide, each of which wt% is based on the total weight of the polyamide composition.
[0053] The polyamide polymer may comprise at least one semi-aromatic polyamide and at least one aliphatic polyamide. In such cases, the weight ratio of the at least one semi-aromatic polyamide based on the total weight of the separate polyamides in the polyamide composition may be less than the weight ratio of the at least one aliphatic polyamide based on the total weight of the separate polyamides in the polyamide composition.
[0054] In some embodiments, the polyamide composition may be free of aromatic polyamides.
[0055] In an alternative embodiment, the polyamide composition may be free of aliphatic polyamides.
[0056] Polyamide compositions may exclude polyamides made from a single monomer, such as PA6.
[0057] Polyamide compositions may exclude polyamides made from two monomers containing six or fewer carbons, such as PA66.
[0058] The polyamide polymer is preferably a semi-crystalline polyamide.
[0059] At least a portion of the polyamide polymers in the polyamide composition may be bio-derived.
[0060] The polyamide composition may include any polyamide having a Tg less than 80°C and / or a Tm less than 250°C.
[0061] Alternatively, the polyamide composition may comprise a polyamide polymer having a Tg of at least 80°C, at least 95°C, or at least 100°C.
[0062] The polyamide polymer may have a Tg of 200° C. or less, 180° C. or less, 160° C. or less, 150° C. or less, 140° C. or less, or 135° C. or less. In such cases, the polyamide polymer may have a Tg of 80° C. to 150° C., 100° C. to 140° C., or 100° C. to 135° C.
[0063] The polyamide polymer may have a melting temperature Tm of at least 230° C., at least 260° C., or at least 265° C. The polyamide polymer may have a Tm of 360° C. or less, 350° C. or less, or 340° C. or less, or 330° C. or less. In such cases, the polyamide polymer may have a Tm of 230° C. to 360° C., 260° C. to 350° C., or 265° C. to 330° C. Tg and Tm may be measured according to ASTM D3418.
[0064] Conductive Materials The polyamide composition also includes from greater than 1% to 20% by weight of at least one electrically conductive material including carbon fibers, carbon nanotubes, or any combination thereof, which imparts improved ESD to the polyamide composition and to articles or devices made from or incorporated with the polyamide composition.
[0065] The conductive material is preferably 2·10 -2 Less than Ω.cm or 1·10 -2 Ω.cm or less, or 5·10 -3 Ω.cm or less, or 3·10 -3 Ω.cm or less, or 2·10 -3 The conductive material preferably has a volume resistivity of at least 1·10 -4 Conductive materials have a volume resistivity of 1·10 -4 Ω.cm to 20·10 -4 It may have a volume resistivity of up to Ω.cm.
[0066] Conductive materials must be at least 0.1 m 2 / g, preferably 10m 2 / g or more, e.g. 10m 2 / g~about 500m 2 The specific surface area (SSA) may be measured by standard Brunauer-Emmett-Teller (BET) measurement of 100 / g. For example, BET measurement using a Micro-metrics TriStar II equipped with a standard nitrogen system may be used.
[0067] The conductive material can comprise or consist essentially of a carbon-based structure selected from the group consisting of metallized carbon fiber, chopped carbon fiber, milled carbon fiber, granular milled / chopped carbon fiber, carbon nanotubes, such as single-walled carbon nanotubes ("SWCNT"), double-walled carbon nanotubes ("DWCNT"), multi-walled carbon nanotubes ("MWCNT") (comprised of nested SWCNT), and any mixtures thereof. The conductive material preferably comprises or consists essentially of a carbon-based structure selected from the group consisting of chopped carbon fiber, milled carbon fiber, granular milled / chopped carbon fiber, carbon nanotubes, and any mixtures thereof.
[0068] Preferred carbon fibers include, but are not limited to, chopped carbon fiber, milled carbon fiber, and / or granular milled / chopped carbon fiber.
[0069] Preferred chopped carbon fibres compatible with polyamide are available from Procotex as CF.OS.U1-6mm, CF.OS.U2-6mm, CF.OS.A-6mm, and CF.OS.I-6mm, with an average monofilament diameter of 7 microns, an average length of 6mm, and a 15·10 -4 Ω.cm to 20·10 -4 It has a volume resistivity of up to
[0070] A preferred milled carbon fiber is commercially available from Procotex as CF.LS-MLD80 to CF.LS-MLD250 and has an average monofilament diameter of 7 microns, a mid-length of 80 to 250 mm, and a tensile strength of 15-100 MPa. -4 Ω.cm to 20·10 -4 It has a volume resistivity of up to
[0071] Carbon nanotubes are an example of a nanometer or molecular-sized conductive material. Preferably, the carbon nanotube is a MWCNT. Carbon nanotubes and carbon nanoropes, such as ropes of carbon nanotubes (e.g., SWNT or MWNT, and ropes of SWNT or MWNT), exhibit high mechanical strength, electrical conductivity, and high thermal conductivity.
[0072] Suitable multi-walled CNTs (MWCNTs) include Nanocyl® NC7000 MWCNT grade with a C purity as low as 90% or Nanocyl® NC3100 MWCNT grade with a C purity greater than 95%, both from Nanocyl (Belgium). Nanocyl® NC7000 MWCNT has an average diameter of 9.5 nanometers, an average length of 1.5 microns, and a length of 250-300 m. 2 / g BET surface area, and 1·10 -4 They have a volume resistivity of Ω.cm. Another suitable source of carbon nanotubes is FRIBIL® multi-walled carbon nanotubes from Hyperion Catalysis International. These MWCNTs can have an outer diameter of about 10 nanometers and lengths of greater than 10 microns.
[0073] Carbon nanotubes may have an average aspect ratio, defined as length to diameter, of 100 or more. Carbon nanotubes may have an average aspect ratio of 1000 or more. Carbon nanotubes may have an average diameter of 1 nanometer (nm) to 3.5 nm or 4 nm (rope). Carbon nanotubes may have an average length of at least 1 μm.
[0074] The conductive material may further comprise other three-dimensional structures selected from the group consisting of fibers, flakes, powders, microspheres, nanoparticles, nanofibers, nanoflakes, nanoropes, nanoribbons, nanofibrils, nanoneedles, nanosheets, nanorods, carbon nanocones, carbon nanoscrolls, nanoplatelets, nanodots, dendrites, discs, or any other three-dimensional body, either alone or in combination.
[0075] Alternatively or additionally, the conductive material may further comprise at least one material selected from metal flakes, metal powders, metallized glass spheres, metallized glass fibers, metal fibers, metallized whiskers, inherently conductive polymers, and / or graphite fibrils.
[0076] The conductive material is preferably composed exclusively of carbon-based structures. Carbon-based structures generally contain at least 90% by weight of carbon. Commercially available industrial grade carbon-based structures or nanostructures with a C purity of 90-95% can be directly dispersed in polyamide polymers without pretreatment.
[0077] In addition to carbon fibers and / or carbon nanotubes, the conductive material may further comprise carbon-based structures selected from carbon nanofibers, carbon nanoflakes, carbon nanoropes, carbon nanoribbons, carbon nanofibrils, carbon nanoneedles, carbon nanosheets, carbon nanorods, carbon nanocones, carbon nanoscrolls, carbon nanoohms, conductive carbon black powders, graphite fibrils, graphite nanoplatelets, nanodots, graphene, or any combination of two or more thereof.
[0078] The conductive material is preferably carbon-based structures selected from the group consisting of carbon fibers, carbon nanotubes (CNTs), such as SWCNTs, DWCNTs, MWCNTs, and any combination thereof; Optionally, carbon nanotube ropes, carbon black powder, or any combination thereof. It comprises or consists of:
[0079] The content of the conductive material in the polyamide composition is more than 1 wt. %, or at least 1.5 wt. % and at most 20 wt. %, based on the total weight of the polyamide composition.
[0080] When the conductive material comprises carbon fibers, the content of carbon fibers in the polyamide composition is at least 6 wt%, or at least 8 wt%, or at least 10 wt%, based on the total weight of the polyamide composition. In such cases, the content of carbon fibers is up to 20 wt%, or up to 17 wt%, or up to 15 wt%, based on the total weight of the polyamide composition. The content of carbon fibers may be 6 wt% to 20 wt%, or 8 wt% to 20 wt%, or 10 wt% to 20 wt%, or 6 wt% to 15 wt%, or 8 wt% to 15 wt%, or 10 wt% to 20 wt%, or 10 wt% to 15 wt%, based on the total weight of the polyamide composition.
[0081] When the conductive material comprises carbon nanotubes, their content in the polyamide composition is greater than 1 wt%, or at least 1.5 wt%, based on the total weight of the polyamide composition. In such cases, the content of carbon nanotubes (CNTs) is up to 8 wt%, or up to 7 wt%, or up to 6 wt%, or up to 5 wt%, or up to 4 wt%, or up to 3 wt%, based on the total weight of the polyamide composition. The content of carbon nanotubes, when present in the polyamide composition, may be greater than 1 wt% to 8 wt%, or greater than 1 wt% to 5 wt%, or greater than 1 wt% to 4 wt%, or greater than 1 wt% to 3 wt%, or 1.5 wt% to 8 wt%, or 1.5 wt% to 5 wt%, or 1.5 wt% to 3 wt%, based on the total weight of the polyamide composition.
[0082] When the conductive material further comprises carbon black powder, the content of the carbon black powder in the polyamide composition may be 0.1 wt.%, or at least 0.5 wt.%, or at least 1 wt.%, based on the total weight of the polyamide composition. In such cases, the content of the carbon black powder in the polyamide composition is up to 10 wt.%, based on the total weight of the polyamide composition.
[0083] When the conductive material further comprises other carbon-based nanostructures (other than carbon nanotubes), their content in the polyamide composition may be 0.1 wt% to 5 wt%, or 0.1 wt% to 4 wt%, or 0.1 wt% to 3 wt%, or 0.5 wt% to 5 wt%, or 0.5 wt% to 4 wt%, or 0.5 wt% to 3 wt%, or 1 wt% to 8 wt%, or 1 wt% to 5 wt%, or 1 wt% to 4 wt%, or 1 wt% to 3 wt%, or 1.5 wt% to 8 wt%, or 1.5 wt% to 5 wt%, or 1.5 wt% to 3 wt%, based on the total weight of the polyamide composition.
[0084] Glass Filler The polyamide composition also contains 20% to 60% by weight of at least one glass filler having a three-dimensional structure characterized by an average length of up to 500 microns, or up to 450 microns, or up to 400 microns, or up to 350 microns, or up to 200 microns, or up to 250 microns. For glass fillers having a three-dimensional structure, the "length" is considered to be the longest dimension. The weight percentages are based on the total weight of the polyamide composition.
[0085] The glass filler is preferably, typically, 10 +12 Over Ω.cm or 5·10 +12 It is an electrically insulating filler with a volume resistivity of more than Ω.cm.
[0086] The glass filler is preferably non-fibrous. A "non-fibrous" filler is herein considered to have a three-dimensional structure with length, width, and thickness, and both length and width are significantly greater than its thickness. In general, such glass fillers with three-dimensional structure have an aspect ratio of up to 3, or up to 2.5, or up to 2, or up to 1.5, with aspect ratio being defined as the average length to the maximum of the average width and average thickness.
[0087] The dimensions (length, width, thickness) of three-dimensional structures can be determined by direct measurement of micrographs obtained by scanning electron microscopy (SEM).
[0088] The average dimensions (i.e., length, width, and thickness) of the three-dimensional structure of the glass filler can be the average length of the glass filler before it is incorporated into the polyamide composition, or it can be the average dimensions of the glass filler in the polyamide composition.
[0089] Glass fiber is a silica-based glass compound containing several metal oxides that can be tailored to form various types of glass. The main oxide is silica in the form of silica sand, and other oxides such as calcium, sodium and aluminum are incorporated to lower the melting temperature and prevent crystallization. Any glass type such as A, C, D, E, M, S, R, T glass or a mixture thereof, preferably C or E glass, can be used for the glass filler. C glass contains alkali components and has high acid resistance. E glass contains almost no alkali, so it has high stability in resins and does not conduct electricity.
[0090] The glass filler comprises at least 20% by weight of glass flakes, based on the total weight of the polyamide composition.
[0091] The glass filler may consist essentially of glass flakes, such that the polyamide composition comprises 20% to 60% by weight glass flakes, preferably 30% to 55% by weight glass flakes, based on the total weight of the polyamide composition.
[0092] The glass flake may be glass flake having C or E glass. Suitable glass flakes including E or C glass are commercially available from NSG under the trademark GLASFLAKE. E-glass flakes are particularly useful for preventing warping and improving dimensional accuracy of precision parts made from thermoplastic polymers. FINEFLAKE glass flakes having an average thickness of 0.4 to 1 micron, also available from NSG, are suitable for fine thin moulded articles. The glass flake may be granulated. For example, FLEKA granulated glass flakes including E glass are commercially available from NSG.
[0093] The glass flakes may have an average thickness of 0.4 microns to 10 microns, in some embodiments, the glass flakes may have an average thickness of 0.4 microns up to 2 microns, or up to 1 micron.
[0094] The glass filler may further comprise chopped glass fibers, so long as the average length is at most 500 microns, or at most 450 microns, or at most 400 microns, or at most 350 microns, or at most 200 microns, or at most 250 microns.
[0095] When the glass filler comprises both glass flakes and chopped glass fibers, both characterized by an average length of at most 500 microns, or at most 450 microns, or at most 400 microns, or at most 350 microns, or at most 200 microns, or at most 250 microns, the combined amount thereof does not exceed 60 wt. %, based on the total weight of the polyamide composition.
[0096] Furthermore, when the glass filler comprises both glass flakes and chopped glass fibers, the glass flakes preferably constitute a weight fraction of the glass filler of more than 50% by weight, or more than 60% by weight, or more than 70% by weight, or more than 80% by weight (weight fractions in weight percent are based on the combined weight of glass flakes and chopped glass fibers). As an example, if the glass flake content in the polyamide composition is 30% by weight, the chopped glass fiber content should be less than 30% by weight (based on the total weight of the polyamide composition).
[0097] The chopped glass fibers, when present in the glass filler, may typically have a thickness of 5 to 20 μm, preferably 5 to 15 μm, more preferably 5 to 10 μm. The chopped glass fibers may have an average length of at least 50 microns, or at least 100 microns, or at least 150 microns, or at least 200 microns, or at least 250 microns. The chopped glass fibers may have an average length of 100 to 500 microns, or 150 to 450 microns.
[0098] The chopped glass fibers may have an aspect ratio of up to 5, or up to 3, or up to 2.5, or up to 2, or up to 1.5, the aspect ratio being defined as the average length relative to the maximum of the average width and average thickness.
[0099] The shape of the chopped glass fiber is not particularly limited. The chopped glass fiber can have a circular cross section ("round glass fiber") or a non-circular cross section ("flat glass fiber"). Examples of suitable flat glass fibers include, but are not limited to, glass fibers having oval, elliptical and rectangular cross sections.
[0100] When the glass filler further comprises flat chopped glass fibers, the flat glass fibers have an average width (longest cross-sectional dimension) of at least 15 μm, preferably at least 20 μm, more preferably at least 22 μm, and even more preferably at least 25 μm. Additionally or alternatively, in some embodiments, the flat chopped glass fibers have an average width (longest cross-sectional diameter) of at most 40 μm, preferably at most 35 μm, more preferably at most 32 μm, and even more preferably at most 30 μm. The flat chopped glass fibers may have an average width (longest cross-sectional diameter) in the range of 15 to 35 μm, preferably 20 to 30 μm, and even more preferably 25 to 29 μm. The flat chopped glass fibers may have a thickness (shortest cross-sectional diameter) of at least 4 μm, preferably at least 5 μm, more preferably at least 6 μm, and even more preferably at least 7 μm. Additionally or alternatively, the flat chopped glass fibers may have a thickness (shortest cross-sectional diameter) of up to 25 μm, preferably up to 20 μm, more preferably up to 17 μm, and even more preferably up to 15 μm. The flat chopped glass fibers may have a thickness (shortest cross-sectional diameter) in the range of 5 to 20 μm, preferably 5 to 15 μm, and more preferably 7 to 11 μm.
[0101] The flat chopped glass fibers may have a ratio of the width (longest diameter in the same cross section) to the thickness (shortest diameter in the same cross section) of the glass fiber of at least 2, preferably at least 2.2, more preferably at least 2.4, and even more preferably at least 3. Additionally or alternatively, the flat chopped glass fibers may have a ratio of the width (longest diameter in the same cross section) to the thickness (shortest diameter in the same cross section) of the glass fiber of at most 8, preferably at most 6, and more preferably at most 4. The flat chopped glass fibers may have a ratio of the width (longest diameter in the same cross section) to the thickness (shortest diameter in the same cross section) of the glass fiber of 2 to 6, preferably 2.2 to 4.
[0102] The glass filler content in the polyamide composition is at least 20 wt%, or at least 25 wt%, or at least 30 wt%, based on the total weight of the polyamide composition. The glass filler content is up to 60 wt%, or up to 55 wt%, or up to 50 wt%, based on the total weight of the polyamide composition. The glass filler content in the polyamide composition may be 20 wt% to 60 wt%, or 25 wt% to 60 wt%, or 30 wt% to 60 wt%, or 20 wt% to 55 wt%, or 25 wt% to 55 wt%, or 30 wt% to 55 wt%, or 20 wt% to 50 wt%, or 25 wt% to 50 wt%, or 30 wt% to 50 wt%, based on the total weight of the polyamide composition.
[0103] The polyamide composition comprises at least 20 wt.%, or at least 25 wt.%, or at least 30 wt.% of glass flakes, based on the total weight of the polyamide composition. The polyamide composition comprises up to 60 wt.%, or up to 55 wt.%, or up to 50 wt.% of glass flakes, based on the total weight of the polyamide composition.
[0104] The glass flake content in the polyamide composition may be 20% by weight to 60% by weight, or 25% by weight to 60% by weight, or 30% by weight to 60% by weight, or 20% by weight to 55% by weight, or 25% by weight to 55% by weight, or 30% by weight to 55% by weight, or 20% by weight to 50% by weight, or 25% by weight to 50% by weight, or 30% by weight to 50% by weight, based on the total weight of the polyamide composition.
[0105] Optional Enhancers The polyamide composition may further comprise at least one optional reinforcing agent different from the glass filler, as described above.
[0106] A wide selection of reinforcing agents, also called reinforcing fillers, may optionally be added to the polyamide composition according to the invention. They may be chosen from fibrous and particulate reinforcing agents.
[0107] The optional reinforcing agents may be selected from inorganic fillers (such as talc, mica, kaolin, calcium carbonate, calcium silicate, magnesium carbonate, etc.), carbon fibres, synthetic polymer fibres, aramid fibres, aluminium fibres, titanium fibres, magnesium fibres, boron carbide fibres, rock wool fibres, steel fibres, wollastonite, glass balls (e.g. hollow glass microspheres) and glass fibres different from the glass fillers used in the polyamide composition according to the invention.
[0108] The particulate reinforcing agents can be selected from inorganic fillers (such as talc, mica, kaolin, calcium carbonate, calcium silicate, magnesium carbonate, etc.) or glass balls (eg hollow glass microspheres).
[0109] As used herein, fibrous reinforcing fillers are considered to be three-dimensional materials having a length, width, and thickness, with the average length being significantly greater than both the width and thickness. Generally, such materials have an aspect ratio of at least 5, at least 10, at least 20, or at least 50, with the aspect ratio being defined as the ratio between the average length and the maximum of the average width and thickness.
[0110] The optional reinforcing fibers (e.g., glass fibers) may be chopped glass fibers (different from glass fillers) having an average length of more than 0.5 mm, preferably at least 1 mm, and up to 50 mm, or may be continuous glass fibers. The average length of the optional reinforcing glass fibers may be the average length of the reinforcing glass fibers before they are incorporated into the polyamide composition, or it may be the average length of the reinforcing fibers in the polyamide composition.
[0111] The optional glass fibers may have an average length of 3 mm to 50 mm, or 3 mm to 10 mm, 3 mm to 8 mm, 3 mm to 6 mm, or 3 mm to 5 mm. Alternatively, the optional glass fibers may have an average length of 10 mm to 50 mm, 10 mm to 45 mm, 10 mm to 35 mm, 10 mm to 30 mm, 10 mm to 25 mm, or 15 mm to 25 mm. In such cases, the optional glass fibers may generally have an equivalent diameter of 5 to 20 μm, preferably 5 to 15 μm, and more preferably 5 to 10 μm.
[0112] All glass types, such as A, C, D, E, M, S, R, T glass, or any mixture thereof, or mixtures thereof, can be used. E, R, S and T glass fibers are known in the art. They are described, among others, in Fiberglass and Glass Technology, Wallenberger, Frederick T.; Bingham, Paul A. (Eds.), 2010, XIV, chapter 5, pages 197-225. R, S and T glass fibers are essentially composed of oxides of silicon, aluminum and magnesium. In particular, they typically contain 62-75% by weight of SiO2, 16-28% by weight of Al2O3 and 5-14% by weight of MgO. On the other hand, R, S and T glass fibers contain less than 10% by weight of CaO.
[0113] The optional glass fiber may comprise or be composed of high modulus glass fiber. High modulus glass fiber has a modulus of elasticity of at least 76 GPa, preferably at least 78 GPa, more preferably at least 80 GPa, and most preferably at least 82 GPa, measured according to ASTM D2343. Examples of high modulus glass fiber include, but are not limited to, S, R, and T glass fibers. Commercially available sources of high modulus glass fiber are S-1 and S-2 glass fibers provided by Taishan and AGY, respectively.
[0114] The optional glass fibers may include or consist of round or flat glass fibers. Examples of suitable flat glass fibers include, but are not limited to, glass fibers having oval, elliptical and rectangular cross sections.
[0115] When the polyamide composition further contains flat glass fibers, the flat glass fibers may have a cross-sectional longest diameter of at least 15 μm, preferably at least 20 μm, more preferably at least 22 μm, and even more preferably at least 25 μm. Additionally or alternatively, the flat glass fibers may have a cross-sectional longest diameter of at most 40 μm, preferably at most 35 μm, more preferably at most 32 μm, and even more preferably at most 30 μm. In some embodiments, the flat glass fibers may have a cross-sectional shortest diameter of at least 4 μm, preferably at least 5 μm, more preferably at least 6 μm, and even more preferably at least 7 μm. Additionally or alternatively, the flat glass fibers may have a cross-sectional shortest diameter of at most 25 μm, preferably at most 20 μm, more preferably at most 17 μm, and even more preferably at most 15 μm.
[0116] The optional flat glass fibers may have a ratio of the longest diameter in a cross-section of the glass fiber to the shortest diameter in the same cross-section of at least 2, preferably at least 2.2, more preferably at least 2.4, and even more preferably at least 3. Additionally or alternatively, this ratio for the flat glass fibers may be at most 8, preferably at most 6, and more preferably at most 4.
[0117] When the optional fibers are circular glass fibers, the glass fibers may have a ratio of the longest diameter in a cross section of the glass fiber to the shortest diameter in the same cross section of less than 2, preferably less than 1.5, more preferably less than 1.2, even more preferably less than 1.1, and most preferably less than 1.05. Of course, those skilled in the art will understand that regardless of the morphology of the glass fiber (e.g., circular or flattened), by definition, the aspect ratio cannot be less than 1.
[0118] The optional glass fibers may be round or flat glass fibers selected from the group consisting of E-glass fibers; high modulus glass fibers having a tensile modulus of at least 76 GPa as measured according to ASTM D2343; and combinations thereof.
[0119] When the polyamide composition comprises glass fillers and at least one optional reinforcing agent according to the above description, the total content of glass fillers + optional reinforcing agents is at least 15 wt%, or at least 20 wt%, or at least 25 wt%, or at least 30 wt%, based on the total weight of the polyamide composition. In additional or alternative embodiments, the total content of glass fillers + optional reinforcing agents is up to 60 wt%, or up to 55 wt%, or up to 50 wt%, based on the total weight of the polyamide composition. In some embodiments, the total content of glass filler plus optional reinforcing agent is from 15% to 60% by weight, or from 20% to 60% by weight, or from 25% to 60% by weight, or from 30% to 60% by weight, or from 20% to 55% by weight, or from 25% to 55% by weight, or from 30% to 55% by weight, or from 20% to 50% by weight, or from 25% to 50% by weight, or from 30% to 50% by weight, based on the total weight of the polyamide composition.
[0120] When the polyamide polymer comprises glass filler plus optional reinforcing agents, the weight ratio of the glass filler based on the total weight of the glass filler plus optional reinforcing agents in the polyamide composition is greater than the weight ratio of the optional reinforcing agents based on the total weight of the glass filler plus optional reinforcing agents in the polyamide composition.
[0121] The polyamide composition is preferably free of fibrous reinforcing agents.
[0122] The polyamide composition preferably excludes glass fibres having an average length of more than 0.5 mm, or more than 1 mm.
[0123] The polyamide composition preferably excludes glass spheres or balls, in particular hollow glass balls.
[0124] The polyamide composition preferably excludes reinforcing agents other than the glass fillers mentioned above.
[0125] Optional Additives Optionally, the polyamide composition may further comprise an additive selected from the group consisting of tougheners, plasticizers, light stabilizers, ultraviolet light ("UV") stabilizers, heat stabilizers, pigments, dyes, antistatic agents, flame retardants, impact modifiers, lubricants, nucleating agents, antioxidants, processing aids, and any combination of two or more thereof.
[0126] When the polyamide composition includes one or more optional additives, the total concentration of the additives is 15 wt% or less, 10 wt% or less, 5 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, and / or at least 0.1 wt%, or at least 0.2 wt%, or at least 0.3 wt%.
[0127] In particular, the polyamide composition may further comprise at least one impact modifier, heat stabilizer, and / or lubricant.
[0128] The impact modifiers useful herein are not particularly limited, so long as they provide useful properties to the polyamide composition, such as sufficient tensile elongation at yield and break. For example, any rubbery low modulus functionalized polyolefin impact modifier having a glass transition temperature below 0°C is suitable for the present invention. Useful impact modifiers include polyolefins, preferably functionalized polyolefins, especially elastomers such as SEBS and EPDM.
[0129] Useful functionalized polyolefin impact modifiers include maleated polypropylene and ethylene-propylene copolymers available as EXXELOR™ PO, and maleic anhydride functionalized ethylene-propylene copolymer rubber containing about 0.6 weight percent pendant succinic anhydride groups, such as EXXELOR® RTM.VA 1801, from Exxon Mobil Chemical Company; acrylate modified polyethylenes available as SURLYN®, such as SURLYN® 9920, a methacrylic acid modified polyethylene, from DuPont Company; and PRIMACOR®, such as PRIMACOR® 1410 XT, an acrylic acid modified polyethylene, from Dow Chemical Company; maleic anhydride modified styrene-ethylene-butylene-styrene (SEBS) block copolymers, in which the SEBS is grafted with about 2 weight percent maleic anhydride, such as KRATON® FG1901 or FG1901X, available from Kraton Polymers; Maleic anhydride functionalized ethylene-propylene-diene monomer (EPDM) terpolymer rubbers are available from commercial sources, including maleic anhydride functionalized ethylene-propylene-diene monomer (EPDM) terpolymer rubbers, such as ROYALTUF® 498, an EPDM functionalized with 1% maleic anhydride, available from Royal Tuf Corporation.
[0130] Other desirable functionalized impact modifiers that can be used in the practice of the present invention include ethylene-higher alpha-olefin polymers and ethylene-higher alpha-olefin-diene polymers that have been provided with reactive functionality by grafting or copolymerizing with a suitable reactive carboxylic acid or derivative thereof, such as, for example, acrylic acid, methacrylic acid, maleic anhydride, or esters thereof, and that will have a tensile modulus of up to about 50,000 psi measured according to ASTM D-638. Suitable higher alpha-olefins include C3-C8 alpha-olefins, such as propylene, butene-1, hexene-1, and styrene. Alternatively, copolymers having structures containing such units can be obtained by hydrogenation of suitable homopolymers and copolymers of polymerized 1-3 diene monomers. For example, polybutadienes with various levels of pendant vinyl units are readily obtained, which can be hydrogenated to obtain ethylene-butene copolymer structures. Similarly, hydrogenation of polyisoprene can be used to provide the equivalent ethylene-isobutylene copolymers. Functionalized polyolefins that can be used in the present invention include those having a melt index in the range of about 0.5 to about 200 g / 10 min.
[0131] In a preferred embodiment, the polyamide composition does not include an antistatic agent.
[0132] Preparation of polyamide compositions The present invention further relates to a process for the preparation of the polyamide composition as detailed above, said process comprising melt blending at least one polyamide polymer, an electrically conductive material, a glass filler, an optional reinforcing agent different from the glass filler, and any other optional additives such as lubricants, UV stabilizers, heat stabilizers, impact modifiers, etc.
[0133] Any melt blending method may be used to combine the polymeric and non-polymeric ingredients involved in the present invention.
[0134] For example, the polymeric and non-polymeric ingredients can be fed into a melt mixer, such as a single or twin screw extruder, a stirrer, a single or twin screw kneader, or a Banbury mixer, and the addition step can be simultaneous addition of all ingredients or gradual batch-wise addition. When the polymeric and non-polymeric ingredients are added gradually batch-wise, a portion of the polymeric and / or non-polymeric ingredients is added first and then melt mixed with the remaining polymeric and non-polymeric ingredients added thereafter until a well-mixed composition is obtained.
[0135] When the optional reinforcing agent exhibits a long physical form (e.g., long or "endless" fibers), stretch extrusion, pultrusion to form long fiber pellets, or pultrusion to form unidirectional composite tapes can be used to prepare the reinforced composition.
[0136] Articles and uses Another aspect of the present invention provides the use of the polyamide composition in an article.
[0137] The polyamide composition may be desirably formulated into articles, preferably molded articles. Suitable molded articles include electronic equipment components, particularly portable electronic equipment components.
[0138] The articles can be used in, among other things, mobile electronics, LED packaging, electrical and electronic components (such as, but not limited to, power supply unit components for computing, data systems, office equipment, and connectors and contacts compatible with surface mount technology), medical equipment components; electrical protection devices for mini circuit breakers, contactors, switches, and sockets; automotive components, and aerospace components (such as, but not limited to, interior cabin components).
[0139] The term "portable electronic device" is intended to refer to an electronic device that is specifically designed to be carried or held by a person for convenient transport and use in various locations. Representative examples of portable electronic devices may be selected from the group consisting of portable electronic telephones, personal digital assistants, laptop computers, tablet computers, radios, cameras and camera accessories, wearable computing devices (e.g., smart watches, smart glasses, etc.), calculators, music players, global positioning system receivers, portable game consoles and console accessories, hard drives, and other electronic storage devices. Preferred portable electronic devices include laptop computers, tablet computers, mobile phones, and wearable computing devices, such as watches.
[0140] Without being limited thereto, components of portable electronic devices of interest herein include antenna windows, mounting parts, snap-fit parts, inter-movable parts, functional elements, actuating elements, tracking elements, adjustment elements, carrier elements, frame elements, switches, connectors, cables, housings, and any other structural parts other than a housing as used in portable electronic devices, such as speaker parts, etc. In some embodiments, the component of the device can be an attachment component with mounting holes or other fastening devices (including, but not limited to, a snap-fit connector between itself and another component of the portable electronic device, including, but not limited to, a circuit board, a microphone, a speaker, a display, a battery, a cover, a housing, an electrical or electronic connector, a hinge, a wireless antenna, a camera module, a switch, or a switch pad).
[0141] The portable electronic device can be at least a part of the input device.
[0142] A particular aspect of the present invention relates to antistatic components for electronic devices, particularly portable electronic devices. Such antistatic components may be molded articles comprising or made from the polyamide compositions described herein.
[0143] The portable electronic device part may be a housing of the portable electronic device. "Housing of the portable electronic device" refers to one or more of the back cover, front cover, antenna housing, frame, and / or skeleton of the portable electronic device. The housing may be a single item or may include two or more components. "Skeleton" refers to a structural part to which other parts of the device are attached, such as electronics, microprocessor, screen, keyboard and keypad, antenna, battery socket, etc. The skeleton may be an internal part that is not visible or only partially visible from the outside of the portable electronic device. The housing may provide protection of the internal parts of the device from impact and contamination and / or damage by environmental agents (such as liquids, dust, etc.). Housing parts such as covers may also provide substantial or primary structural support for certain parts exposed to the outside of the device, such as the screen and / or antenna, and protection against impact for the certain parts. The housing of the portable electronic device may be selected from the group consisting of a mobile phone housing, an antenna housing, an antenna window, a tablet housing, a laptop computer housing, a tablet computer housing, or a watch housing.
[0144] The electronic device component may include, for example, a wireless antenna or a camera module. In this case, the wireless antenna may be a WiFi antenna or an RFID antenna. In some such embodiments, at least a portion of the wireless antenna is disposed on the polyamide composition. Additionally or alternatively, at least a portion of the wireless antenna may be replaced by the polyamide composition.
[0145] The description of a "portable" electronic device component applies equally to electronic device components (such as housings, radio antennas, camera modules, etc.) that are part of an electronic device that is not "portable," i.e., not carried or held by a person.
[0146] Examples of automotive parts include, but are not limited to, automotive electronics parts, automotive lighting parts (such as, but not limited to, motor end caps, sensors, ECU housings, bobbins and solenoids, connectors, circuit protection / relays, actuator housings, Li-ion battery systems, and fuse boxes), traction motors and power electronics parts (such as, but not limited to, battery packs), battery housings.
[0147] Articles can be molded from the polyamide compositions by any process suitable for thermoplastics, such as by extrusion, injection molding, blow molding, rotational molding, overmolding, or compression molding.
[0148] Preferred formation of molded articles or (portable) electronic device parts involves suitable melt processing methods such as injection molding or extrusion of the polyamide composition, with injection molding being the preferred molding method.
[0149] In some embodiments, the molded article or (portable) electronic device part according to the invention has at least one of the following properties:
[0150] The articles or (mobile) electronic device parts according to the invention have a resistance to at least 1·10 +5 Ω.cm, or at least 1.5·10 +5 The molded article or (portable) electronic device part according to the invention may have a volume resistivity of 5-10 +12 Ω.cm or less, or 3·10 +12 In such cases, the article or (portable) electronic device part may have a volume resistivity of 1·10 +5 Ω.cm to 5·10 +12 It may have a volume resistivity of up to Ω.cm.
[0151] The molded article or (portable) electronic device part according to the present invention may have a transverse mold shrinkage (%) of 0.5% or less, or 0.47% or less, or 0.45% or less, or 0.44% or less, determined according to ISO294 (ASTM D955).
[0152] The molded article or (portable) electronic device part according to the invention may have a ratio of the mold shrinkage in the machine direction to the shrinkage in the transverse direction of more than 32%, or more than 35%, or more than 40%, or more than 45%, or more than 50%, or more than 55%, or more than 60%, where the mold shrinkage in the machine direction and the transverse direction (%) is determined according to ISO 294 (ASTM D955).
[0153] The moulded article or (portable) electronic device part according to the present invention may have a warpage of 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.18 or less.
[0154] Use of the polyamide composition In some embodiments, the polyamide compositions or articles may be used to manufacture the portable electronic device components described above.
[0155] Method for reducing warpage and / or mold shrinkage of polyamide compositions Another aspect of the invention relates to a method for reducing warpage and / or mold shrinkage of a molded article made from a polyamide composition comprising blending a polyamide polymer and a conductive material with a glass filler and optional ingredients to form a molding composition and then molding, preferably injection molding, the molding composition to form a molded article. The blending is preferably done by melt blending as described above.
[0156] Method for reducing the volume resistivity of a polyamide composition Another aspect of the invention relates to a method for reducing the volume resistivity of a molded article made from a polyamide composition comprising blending a polyamide polymer and a glass filler and optional ingredients with a conductive material to form a molding composition and then molding, preferably injection molding, the molding composition to form a molded article. The blending is preferably done by melt blending as described above. EXAMPLES
[0157] The present invention will now be described with reference to the following examples, which are for illustrative purposes only and are not intended to limit the scope of the invention. As used in the examples, "E" refers to an example embodiment of the invention and "CE" refers to a counterexample.
[0158] The examples demonstrate the improvement in warpage and / or mold shrinkage and CLTE (due to dimensional stability) and reduced volume resistivity of the polyamide compositions according to the invention.
[0159] raw materials The raw materials used to form the samples are as follows: Polyamide 1 ("PA1"): PA6,10 (Tg=50-60°C, Tm=220°C), available from Radici as Radipol DC40 Polyamide 2 ("PA2"): PA10T / 10I (Tg=105°C, Tm=295°C), as Vicnyl 6100, from Kingfa Glass flakes ("GFla"): MEG160FY-M03, from NEG Glass fiber ("GFib1") - CSG3PA flat E-glass fiber, from Nittobo Fiberglass ("GFib2") - HM435TM round S-1 glass from Taishan Conductive material ("CM1"): APPLY CARBON chopped carbon fiber CF.OS.U1-6MM, from Procotex Optional Conductive Material ("CM2"): Carbon black concentrate (30% by weight of Black Pearls 800 carbon black, 70% by weight of PAMXD6 as the polymeric carrier), commercially available as IXEF® 0316 / 0000; A15560; from Colloids Limited Conductive Material ("CM3"): Polymer Carrier from Mitsubishi Gas Chemical Co., Inc.: Masterbatch of 15% by weight of Hyperion Catalysis International's FIBRIL® multi-walled carbon nanotubes in PAMXD6 "7003" Conductive material ("CM4"): Polymer carrier from Mitsubishi Gas Chemical Co., Inc.: Masterbatch of 10% by weight of Nanocyl® NC7000 multi-walled carbon nanotubes in PAMXD6 "7003" Conductive material ("CM5"): granular 300 micron milled carbon fiber, commercially available from Procotex as APPLY CARBON CF MLD 300G U1 recycled carbon fiber granules; having an average size of about 300±40 microns, a carbon content of about 94% by weight, a monofilament fiber diameter of about 7±2 microns, and a fiber length of about 15-10 mm. -3 It is characterized by its average volume resistivity in Ω.m. Additives: Additive package 1 ("AP1") containing 0.1 wt. % lubricant (calcium stearate Ceasit I from Baerlocher) and 0.2 wt. % heat stabilizer (Irganox® B1171 from BASF) Additives: Additive package 2 ("AP2") including 0.1 wt. % of a lubricant (calcium stearate Ceasit I, from Baerlocher), 0.3 wt. % of a UV stabilizer (Chimassorb 944 LD, from BASF), and 0.2 wt. % of a heat stabilizer (Irganox® B1171, from BASF). · Optional Additives: Pigments / dyes may be added to the polyamide composition.
[0160] Test Method Tensile properties – ISO527 Tensile modulus, strength, and strain were measured on five injection molded ISO Type 1a tensile specimens (total length = 170 mm, gauge length = 50 mm, test section width = 10 mm, thickness = 4 mm). Notched Izod Impact Strength – ASTM D256 Notched Izod impact strength was measured in J / m on five injection molded rectangular bars having dimensions 3.2 mm thick x 12.7 mm wide x 125 mm long. Unnotched Izod Impact Strength - ASTM D4812 Unnotched Izod impact strength was measured in J / m on five injection molded rectangular bars having dimensions 3.2 mm thick x 12.7 mm wide x 125 mm long. In some cases, Izod impact strength properties (notched Izod, unnotched Izod) are measured in kJ / m using ISO 180 using 10 injection molded ISO Type 1A bars (length 80±2mm, width 10±0.2mm, thickness 4±0.2mm). 2 Measured in units. ·CLTE - ASTM E831 Dimensional changes were measured on injection molded specimens with dimensions of 3.2 mm thickness × 12.7 mm width × 12.0-13.0 mm length. Using a TMA, the CLTE in the machine and transverse directions was measured from 0 to 50 °C at a heating rate of 5 °C / min. Mold shrinkage - ISO294 (ASTM D955) The mold shrinkage (machine direction mold shrinkage (%) and transverse direction mold shrinkage (%)) was measured on five injection molded plaques with dimensions of 60 mm width x 60 mm length x 2 mm thickness. Warpage is determined as follows: Polyamide compositions were injection molded into plaques having dimensions of 60 mm x 60 mm x 2 mm according to ASTM D955, as detailed above. Warpage was calculated as the absolute percent shrinkage in the cross direction minus the percent shrinkage in the machine direction. Volume Resistivity – ASTM D257 Volume resistivity was measured on five injection molded plaques of dimensions 4 inch x 4 inch x 1 / 8 inch (length x width x thickness) or 60 mm x 60 mm x 2 mm (length x width x thickness). ·Surface resistivity - ASTM D257 Surface resistivity was measured on five injection molded plaques measuring 4 inches by 4 inches by 1 / 8 inch (length by width by thickness).
[0161] Example 1 – Polyamide composition containing PA6,10 In this example, multiple samples of polyamide compositions were prepared in which PA1 (PA6,10) was compounded (melt blended) with carbon fiber, optional carbon black concentrate, additive package 1, and glass flake (GFa).
[0162] Samples E1 and E2 contained 44.7 wt% PA1, 10 wt% carbon fiber, and 45 wt% glass flakes. Sample E2 further contained 10 pph of carbon black concentrate, while sample E1 did not contain any carbon black concentrate.
[0163] For comparison, sample CE0 was prepared containing 89.7 wt% PA1 and 10 wt% carbon fiber but no glass flake. Samples CE1 and CE2 were also prepared containing 49.7 wt% PA1, 50 wt% glass flake, and 1 or 10 pph of carbon black concentrate (but no carbon fiber). Samples CE3 and CE4 contained 44.7 wt% PA1, 50 wt% glass flake, and 1 or 10 pph of carbon black concentrate, but contained 5 wt% carbon fiber, half the content used in samples E1 and E2.
[0164] Melt blending was performed using a Coperion® ZSK-26 co-rotating twin screw extruder, and the compounded samples were then molded according to ASTM D3641.
[0165] The polyamide compositions are shown in Table 1, along with the following properties: surface resistivity, volume resistivity, mechanical properties including impact properties, CLTE (0-50°C) properties (ppm in machine and transverse directions), and mold shrinkage properties (in / in%) in machine and transverse directions for the compositions.
[0166] As shown in Table 1, the addition of 10 wt. % carbon fiber to the polyamide composition of samples E1 and E2 reduced not only the volume resistivity but also the surface resistivity compared to samples CE1 and CE2 that did not contain carbon fiber, and samples CE3 and CE4 that contained the same carbon fiber at 5 wt. %. Samples E1 and E2 had a volume resistivity of 10 +5 ~5·10 +12 It was antistatic because it was in the Ω·cm range.
[0167] The introduction of only 10 wt% carbon fiber into PA1 also did not achieve a volume resistivity within the ESD range, as seen for sample CE0 compared to samples E1 and E2. A combination of glass flakes (insulating filler) and carbon fiber was required to produce an ESD material.
[0168] [Table 1]
[0169] The combination of 10 wt% carbon fiber and carbon black in the polyamide composition of sample E2 reduced the volume resistivity by 5 orders of magnitude compared to sample E1, which contained 10 wt% carbon fiber without IXEF® carbon black concentrate. However, this effect was not observed in samples CE2 (without CM1) and CE4 (with 5 wt% CM1), which contained 10 pph of IXEF® carbon black concentrate, compared to samples CE1 (without CM1) and CE2 (with 5 wt% CM1), which contained only 1 pph of IXEF® carbon black concentrate. Thus, the 5·10 +12 In the absence of carbon fiber in the PA1-based composition in an amount sufficient to achieve a volume resistivity of Ω.cm or less (within the ESD volume resistivity range), the addition of 1-10 pph of IXEF® carbon black concentrate was not effective in lowering the volume resistivity of the PA1-based composition to make it suitable for ESD.
[0170] The addition of 5 wt. % carbon fiber to the polyamide composition of sample CE3 slightly decreased the volume resistivity but did not decrease the surface resistivity compared to sample CE1, which did not contain carbon fiber, but in any case, the volume resistivity of sample CE3 was still too high to fall within the range of ESD volume resistivities.
[0171] Furthermore, the elastic modulus and tensile stress at break of samples E1, E2 containing 10 wt.% carbon fiber were improved compared to samples CE3, CE4 containing 5 wt.% carbon fiber, and even better than samples CE1, CE2 containing no carbon fiber.
[0172] The tensile elongation at break (%) of samples E1, E2 containing 10 wt.% carbon fiber was the same or better than samples CE1, CE2 containing no carbon fiber and samples CE3, CE4 containing 5 wt.% carbon fiber.
[0173] In addition, the addition of glass flakes to all PA1-based compositions in Table 1 resulted in more isotropic mold shrinkage properties. The ratio of shrinkage in the machine direction to the cross direction was 74%-82%, very close to isotropic shrinkage. Despite the addition of 10 wt% CM1, the transverse mold shrinkage of the polyamide compositions in samples E1, E2 remained relatively unchanged compared to samples CE1-CE4, indicating that the addition of 10 wt% CM1 did not adversely affect the transverse mold shrinkage.
[0174] Comparing Samples E2 to E1, CE4 to CE3, and CE2 to CE1, the presence of carbon black appeared to slightly reduce the transverse mold shrinkage of the compositions based on PA1.
[0175] The results obtained with samples E1 and E2 demonstrate that by adding more than 5% by weight of carbon fiber (and optional carbon black) and 45% by weight of glass flakes to a composition based on PA1, a suitable ESD material can be obtained while obtaining dimensional stability (while maintaining improved mold shrinkage properties).
[0176] Example 2 - Polyamide composition containing PA10T / 10I In this example, multiple samples of polyamide compositions were prepared in which PA2 (PA10T / 10I) was compounded (melt blended) with carbon fiber, optional carbon black concentrate, additive package 1, and glass flake (GFla).
[0177] Samples E3 and E4 contained 44.7 wt% PA2, 10 wt% carbon fiber, and 45 wt% glass flakes. Sample E4 also contained 10 pph of carbon black concentrate, while sample E3 contained no carbon black concentrate.
[0178] For comparison, sample CE5 was also prepared containing 49.7 wt. % PA2, 50 wt. % glass flake, and 10 pph of carbon black concentrate (but no carbon fiber).
[0179] Samples CE6 and CE7 contained 44.7 wt% PA2, 50 wt% glass flake, and 1 pph or 10 pph of carbon black concentrate, but contained 5 wt% carbon fiber, half the content used in samples E3 and E4.
[0180] Melt blending was performed using a Coperion® ZSK-26 co-rotating twin screw extruder, and the compounded samples were then molded according to ASTM D3641.
[0181] Table 2 shows the compositions of the polyamides of samples E3, E4, CE5, and CE6, along with the following properties: surface resistivity, volume resistivity, mechanical properties, CLTE (0-50°C) properties, and mold shrinkage properties of the compositions.
[0182] Counterexample 3 - Polyamide composition containing PA10T / 10I and glass fibers In this counter example, several samples CE8, CE9 were prepared in which PA2 (PA10T / 10I) was compounded (melt blended) with additive package 2 and either 30 wt% E-glass fiber (GFib1) or 55 wt% S1-glass fiber (GFib2). In these examples, glass fiber was used to evaluate dimensional instability (by mold shrinkage measurements and warpage calculations) compared to glass flakes.
[0183] The compositions and properties of the polyamides of samples CE8 and CE9 are also shown in Table 2.
[0184] As shown in Table 2, the addition of 10 wt. % carbon fiber to the polyamide composition of samples E3 and E4 reduced not only the volume resistivity but also the surface resistivity compared to sample CE5 without carbon fiber and samples CE6 and CE7 containing the same carbon fiber at 5 wt. %. Samples E3 and E4 had a volume resistivity of 10 +5 ~5·10 +12 The electrical resistivity was in the range of Ω.cm and therefore was antistatic. Samples CE5, CE6, and CE7 were not ESD materials.
[0185] The combination of 10 wt% carbon fiber and carbon black in the polyamide composition of sample E4 reduced the volume resistivity by an order of magnitude compared to sample E3, which contained 10 wt% carbon fiber but no carbon black. However, this effect was not observed in sample CE7 (containing 5 wt% CM1) which contained 10 pph of carbon black concentrate compared to sample CE6 (containing 5 wt% CM1) which contained only 1 pph of carbon black concentrate. Thus, the presence of 5·10 pph of carbon black in the composition based on PA2 reduced the volume resistivity by an order of magnitude. +12In the absence of carbon fiber in sufficient amounts to achieve a volume resistivity below Ω.cm (to be within the ESD volume resistivity range), the addition of 1-10 pph of carbon black concentrate was not effective in making the volume resistivity of the PA2 based compositions suitable for ESD. The volume resistivities obtained for samples CE6, CE7 (containing 5 wt% CM1) were still too high to be within the ESD volume resistivity range.
[0186] Furthermore, the elastic modulus of samples E3 and E4 containing 10 wt% carbon fiber was improved compared to samples CE6 and CE7 containing 5 wt% carbon fiber, and was even better than sample CE5 containing no carbon fiber.
[0187] In addition, the mold shrinkage approached isotropy when glass flakes were added for samples CE5-CE7 and E3-E4 in Table 2. The ratio of mold shrinkage in the machine direction to the transverse direction was in the range of 63%-78%.
[0188] Despite the addition of 10 wt% CM1, the transverse mold shrinkage of the polyamide composition in sample E3 remained relatively unchanged compared to samples CE5-CE7, indicating that the addition of carbon fiber did not adversely affect the transverse mold shrinkage.
[0189] [Table 2]
[0190] On the other hand, the addition of glass fibers in samples CE8 (55 wt.% S1-glass fiber) and CE9 (30 wt.% E-glass fiber) made the mold shrinkage anisotropic, as shown in Table 2. The ratio of mold shrinkage in the machine direction to the transverse direction was 13% and 31%, respectively. It was also observed that the warpage of samples CE8 (55 wt.% S1-glass fiber) and CE9 (30 wt.% E-glass fiber) in Table 2 was higher than that observed with the addition of glass flakes in samples CE5-CE7 and E3-E4.
[0191] The results obtained with samples E3 and E4 demonstrate that the addition of more than 5% by weight of carbon fiber (and optional carbon black) and 45% by weight of glass flakes to a PA2 based composition makes it possible to obtain a suitable ESD material while still obtaining dimensional stability (low warpage and improved mold shrinkage properties).
[0192] Example 4 – Polyamide composition containing PA6,10 In this example, multiple samples of polyamide compositions were prepared in which PA1 (PA6,10) was compounded (melt blended) with carbon nanotubes (as masterbatches "CM3" or "CM4"), carbon black concentrate "CM2", additive package 1, and glass flake (GFa). Melt blending was performed using a Coperion® ZSK-26 co-rotating twin screw extruder, and the compounded samples were then molded according to ASTM D3641.
[0193] Samples E5 and E6 contained two different amounts of carbon nanotube masterbatch “CM3” as the conductive material, resulting in actual weight contents of 2.25 wt% and 3 wt% CNT, respectively. Samples E7 and E8 contained two different amounts of carbon nanotube masterbatch “CM4” as the conductive material, resulting in actual weight contents of 1.5 wt% and 2 wt% CNT in PAMXD6 as the polymer carrier, respectively.
[0194] For comparison, a sample CE10 was prepared that did not contain any carbon nanotubes.
[0195] The polyamide compositions are shown in Table 3 along with the following properties: surface resistivity, volume resistivity, mechanical properties including impact properties, CLTE (0-50°C) properties (ppm in machine and transverse directions), and mold shrinkage properties (in / in%) in machine and transverse directions for the compositions.
[0196] [Table 3]
[0197] As shown in Table 3, when 1.5 to 3 wt. % of carbon nanotubes (MWCNT) were added to the polyamide compositions of samples E5 to E8, the volume resistivity decreased compared to sample CE10, which did not contain carbon nanotubes, and the surface resistivity also decreased. Samples E5 to E8 had a volume resistivity of 10 +5 ~5·10 +12 The electrical resistance was in the Ω.cm range and therefore antistatic. Sample CE10 was not an ESD material.
[0198] Although not shown, the addition of less than 1 wt% carbon nanotubes (MWCNTs) to polyamide compositions reduces the volume resistivity to the maximum value of 5·10 for ESD materials. +12 It did not drop below Ω.cm.
[0199] 10 ways to get ESD materials +5 To achieve the minimum volume resistivity in Ω.cm, the weight percentage of carbon nanotubes added to the polyamide composition could be increased beyond 3 weight percent of the CNT content (used in sample E6), such as up to 5 weight percent CNT or up to 6 weight percent CNT, thereby reducing the volume resistivity by at least about two orders of magnitude.
[0200] The results obtained for samples E5-E8 demonstrated that the addition of 1.5-3 wt. % carbon nanotubes and 50 wt. % glass flakes to a composition based on PA1 allows for a suitable ESD material while still providing dimensional stability (low warpage and improved mold shrinkage properties).
[0201] Example 5 - Polyamide composition containing PA10T / 10I In this example, polyamide composition sample E9 was prepared by compounding (melt blending) PA2 (PA10T / 10I) with 10 wt. % milled carbon fiber particulate ("CM5") as the conductive material, carbon black concentrate "CM2", additive package 1, and glass flake (GFla). The melt blending was performed using a Coperion® ZSK-26 co-rotating twin screw extruder, and the compounded sample was then molded according to ASTM D3641.
[0202] For comparison, sample CE11 was prepared that did not contain milled carbon fiber.
[0203] The polyamide compositions and properties of samples CE11 and E9 are shown in Table 4.
[0204] As shown in Table 4, the addition of 10 wt. % milled carbon fiber (in particulate form) to the polyamide composition of sample E9 significantly reduced the volume resistivity by 10 orders of magnitude compared to sample CE11, which did not contain milled carbon fiber. +5 ~5·10 +12 The electrical resistance was in the Ω.cm range and therefore antistatic. Sample CE11 was not an ESD material.
[0205] [Table 4]
[0206] Additionally, the tensile modulus and tensile strength of sample E9, which contained 10 wt% milled carbon fiber, was improved compared to sample CE11, which did not contain milled carbon fiber. Similarly, the notched Izod impact properties were also improved with the addition of milled carbon fiber.
[0207] Additionally, the addition of 10 wt% milled carbon fiber did not adversely affect mold shrinkage or warpage, but rather improved them. The transverse mold shrinkage (0.3%) was significantly improved for sample E9 compared to sample CE11 (0.43%). The ratio of machine to transverse mold shrinkage was 90% compared to 70% for sample CE11, and the estimated warpage value decreased from 0.13 (CE11) to 0.03 (E9). With the addition of 10 wt% milled carbon fiber to sample E9, the mold shrinkage approached isotropy.
[0208] The results obtained with sample E9 demonstrated that the addition of 10 wt. % milled carbon fiber particulate and 50 wt. % glass flake to a PA2 based composition allows for a suitable ESD material to be obtained, with dimensional stability (low warpage and improved mold shrinkage properties) while maintaining excellent mechanical properties.
[0209] Although preferred embodiments of the present invention have been shown and described, modifications thereof may be made by those skilled in the art without departing from the spirit or teachings of the present invention. The embodiments described herein are merely illustrative and not limiting. Many variations and modifications of the compositions, articles, and methods are possible and are within the scope of the present invention. Thus, the scope of protection is not limited to the above-described description, but only by the following claims, the scope of which includes all equivalents of the subject matter of the claims. Each and every claim is incorporated herein as an embodiment of the present invention. Thus, the claims are further explanations and additions to the preferred embodiments of the present invention. Any incorporation by reference of the above documents is limited to not incorporating subject matter contrary to the express disclosure herein.
[0210] The disclosures of all patent applications and publications cited herein are hereby incorporated by reference to the extent that they provide exemplary procedural or other details supplementary to those set forth herein. In the event that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the description of this application to the extent that certain terms may be unclear, the description shall control.
Claims
1. at least 20 weight percent (wt%) of a polyamide polymer; greater than 1% and up to 20% by weight of a conductive material including carbon fibers, carbon nanotubes, or any combination thereof; - 20% to 60% by weight of a glass filler having a three-dimensional structure characterized by an average length of up to 500 microns, the glass filler comprising at least 20% by weight of glass flakes; A polyamide composition comprising: wherein said weight percentages are based on the total weight of said polyamide composition.
2. 2. The polyamide composition of claim 1, wherein the polyamide polymer comprises a semi-aromatic polyamide, preferably a polyphthalamide.
3. 2. The polyamide composition of claim 1, wherein the polyamide polymer comprises a semi-aromatic polyamide selected from the group consisting of PA10T / 10I; PA10T; PA6T / 6I; PA6T; PA9T; PA12T; PA10T / 66; PA6T / 66; PA6,I; PA12I; PAMXD6; PAPXD10; and any combination thereof.
4. 2. The polyamide composition of claim 1, wherein the polyamide polymer comprises an aliphatic polyamide selected from the group consisting of PA610; PA612; PA10 / 10; PA12; PA510; PA66; PA10 / 12; and any combination thereof.
5. 2. The polyamide composition of claim 1, wherein the glass filler further comprises round or flat chopped glass fibers.
6. 2. The polyamide composition of claim 1, wherein the glass filler comprises 30% to 55% by weight of glass flake, based on the total weight of the polyamide composition.
7. 2. The polyamide composition of claim 1, wherein the conductive material comprises chopped carbon fiber, milled carbon fiber, granular milled / chopped carbon fiber, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT), or any combination thereof.
8. 10. The polyamide composition of claim 1, wherein the conductive material further comprises carbon black powder.
9. 2. The polyamide composition of claim 1, wherein the conductive material further comprises carbon-based three-dimensional structures selected from the group consisting of flakes, powders, microspheres, nanoparticles, nanofibers, nanoflakes, nanoropes, nanoribbons, nanofibrils, nanoneedles, nanosheets, nanorods, carbon nanocones, carbon nanoscrolls, nanoplatelets, nanodots, dendrites, discs, or any other three-dimensional bodies, alone or in combination.
10. The conductive material has a resistance of 2.10% or less as measured in accordance with ASTM D257. -2 Less than Ω.cm or 1.10 -2 Ω. cm or less, or 5.10 -3 Ω. cm or less, or 3.10 -3 Ω. cm or less or 1.10 -3 Volume resistivity of less than or equal to Ω.cm, preferably 1.10 as measured according to ASTM D257 -4 Ω.cm to 20.10 -4 2. The polyamide composition of claim 1 having a volume resistivity of up to 1.5 Ω.cm.
11. 10. The polyamide composition of claim 1, which is antistatic.
12. 12. A method for making the polyamide composition of any one of claims 1 to 11, comprising melt blending the polyamide polymer, the conductive material, the glass filler, and optional additives selected from the group consisting of another reinforcing agent different from the glass filler, a toughening agent, a plasticizer, a light stabilizer, a UV stabilizer, a heat stabilizer, a pigment, a dye, an antistatic agent, a flame retardant, an impact modifier, a lubricant, a nucleating agent, an antioxidant, a processing aid, and any combination of two or more thereof.
13. A molded article comprising the polyamide composition of claim 1.
14. A portable electronic device part comprising the polyamide composition of claim 1.
15. The molded article according to claim 13 or the portable electronic device part according to claim 14, having at least one of the following characteristics: 1.10 measured according to ASTM D257 +5 Ω.cm to 5-10 +12 Volume resistivity up to Ω.cm; a ratio of the mold shrinkage in the machine direction to the mold shrinkage in the transverse direction of greater than 32%, or greater than 35%, or greater than 40%, or greater than 45%, or greater than 50%, or greater than 55%, or greater than 60%, wherein the mold shrinkage in the machine direction (%) and the mold shrinkage in the transverse direction (%) are determined according to ISO 294 (ASTM D955); Warpage of 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.18 or less, and / or A percent transverse mold shrinkage, determined according to ISO 294 (ASTM D955), of 0.5% or less, alternatively 0.47% or less, alternatively 0.45% or less, alternatively 0.44% or less.